2011
DOI: 10.1186/1475-2859-10-13
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen transfer rate during the production of alginate by Azotobacter vinelandii under oxygen-limited and non oxygen-limited conditions

Abstract: BackgroundThe oxygen transfer rate (OTR) and dissolved oxygen tension (DOT) play an important role in determining alginate production and its composition; however, no systematic study has been reported about the independent influence of the OTR and DOT. In this paper, we report a study about alginate production and the evolution of the molecular mass of the polymer produced by a wild-type A. vinelandii strain ATCC 9046, in terms of the maximum oxygen transfer rate (OTRmax) in cultures where the dissolved oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 32 publications
1
35
0
Order By: Relevance
“…The result was in accordance with the Lozano et al, (2011). Thus, culture media samples were removed at intervals and quantitative extractions of EPS were made.…”
Section: Resultsmentioning
confidence: 62%
“…The result was in accordance with the Lozano et al, (2011). Thus, culture media samples were removed at intervals and quantitative extractions of EPS were made.…”
Section: Resultsmentioning
confidence: 62%
“…The production of alginates with specific molecular weights for biomaterials with specific applications can be achieved in a bacterial bioprocess. Studies have demonstrated that the culture conditions of agitation rate and oxygen transfer rate (OTR) affect alginate production in bioprocesses [7,15,19]. Peña et al [19] evaluated the effect of agitation rate and dissolved oxygen tension (DOT) and reported that the highest alginate production (5.0 g l -1 ) and molecular weight distribution were found at 3% DOT under a high agitation rate (700 rpm).…”
Section: Introductionmentioning
confidence: 98%
“…In addition, one possible reason might be the variation in the maximum oxygen transfer rate (OTR max ). A very recent study [7] showed that alginate synthesis depends strongly on OTR max even when the DOT was maintained constant at 5% at two different agitation speeds of 300 and 700 rpm. This study reported that the highest alginate concentration, 3.1 g/l, and the maximum specific alginate production rate, 0.031g alg /g bio h, were obtained at OTR max of 100 mmol/l h, which was the highest value observed at 700 rpm.…”
Section: Resultsmentioning
confidence: 98%
“…However, it is critical to keep in mind that since the DOT was not controlled, a combined effect of mixing rate and DOT might be responsible for the results obtained by Parente et al [10] since the uncontrolled DOT might affect the molecular weight of alginates. Recently, it was found that the molecular weight of the alginate was greatly influenced by OTR max , rather than mixing rate [7]. In this study, two different mixing rates, 500 and 700 rpm, corresponding to similar OTR max (90 and 100 mmol/l h, respectively) were investigated.…”
Section: Resultsmentioning
confidence: 99%